Volume 3: Heat Transfer, Parts a and B 2009
DOI: 10.1115/gt2009-59355
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Pre-Swirl Nozzle Location on the Air Transfer System (ATS) Characteristic

Abstract: In most industrial turbines the cooling air for rotating turbine blades, is extracted from the compressor and transferred via passageways in the stationary parts and the rotor to the blade roots. These passages form the stator-rotor air transfer system (ATS). In stationary part of the ATS the air is usually pre-swirled in the direction of rotation to reduce the temperature and to minimize the losses in the transition area. This paper presents the investigations of the impact of the pre-swirl nozzle location on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Granovskiy et al [23] presented a comparison in flow structure and temperature distribution between a radial pre-swirl system and an axial pre-swirl system. The results showed that two pre-swirl systems have very similar characteristics.…”
Section: Introductionmentioning
confidence: 99%